2016
DOI: 10.18632/oncotarget.7979
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment magnetic resonance imaging of regional lymph nodes with carcinoembryonic antigen in prediction of synchronous distant metastasis in patients with rectal cancer

Abstract: Distant metastasis in patients with rectal cancer remains a problem influencing prognosis. Prediction of synchronous distant metastasis is important for the choice of personalized treatment strategies and postoperative follow-up protocol. So far, there are few studies about the predictive value of MRI features combined with clinical characteristics for synchronous distant metastasis in rectal cancer, especially for the lesions developed within 6 months after surgery. We retrospectively reviewed the pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…There is evidence that lymph node metastasis is the main predictor of the prognosis of patients with colorectal cancer [43,44]. It has been suggested that compared with the presence of 1-3 positive lymph nodes (N1 disease, 3-year disease-free survival rate of 83%) and N0 disease (3-year disease-free survival rate of 89%), 4 or more lymph node metastases (N2 disease) Of patients, the 3-year disease-free survival rate (75%) is lower [45]. Therefore, whether it is to identify the presence or absence of lymph node metastasis or to accurately distinguish the number of metastatic lymph nodes is very valuable to the prognosis of patients with rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that lymph node metastasis is the main predictor of the prognosis of patients with colorectal cancer [43,44]. It has been suggested that compared with the presence of 1-3 positive lymph nodes (N1 disease, 3-year disease-free survival rate of 83%) and N0 disease (3-year disease-free survival rate of 89%), 4 or more lymph node metastases (N2 disease) Of patients, the 3-year disease-free survival rate (75%) is lower [45]. Therefore, whether it is to identify the presence or absence of lymph node metastasis or to accurately distinguish the number of metastatic lymph nodes is very valuable to the prognosis of patients with rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are still disputes about the value of ACT for locally advanced rectal cancer patients who received neoadjuvant CRT and surgery. Serum CEA is the most important tumor marker for the presence of subclinical hepatic or pulmonary metastases, and elevated pretreatment serum CEA levels were significantly associated with poor prognosis in rectal cancer patients (20,21). Besides, serum CEA levels could predict PCR after neoadjuvant therapy for rectal cancer (22).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that elevated CEA before treatment and positive lymph node staging on magnetic resonance imaging were independent risk factors for synchronous distant metastasis in rectal cancer. [ 23 ] The combination of both risk factors could indicate patients at high risk and candidates for structured personalized treatment. In the present study, the clinicopathological correlation analysis showed that NSE was significantly associated with vascular invasion and nerve infiltration.…”
Section: Discussionmentioning
confidence: 99%